Penguatan Religiusitas Melalui Program Pembiasaan Di SMP BPPI Bojong Berbasis Kurikulum Merdeka - Gilang Sukma Permana; Asep Nursobah; Mohammad Erihadiana (Jurnal Kajian Islam dan Sosial Keagamaan, 2025)
Education is a learning process that helps students understand, comprehend, and think more critically. This study aims to examine the aspect of religiosity in the Habituation Program implemented at SMP BPPI Bojong using the Merdeka Curriculum approach. The research method employed is descriptive qualitative, with data collection techniques including literature studies, observations, and interviews. Religiosity in this Habituation Program encompasses aspects of faith, piety, and noble character, alongside the reinforcement of global diversity values, independence, mutual cooperation, and creativity.